2022
DOI: 10.1097/ta.0000000000003596
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods end-user assessment to determine the ideal supraglottic airway device for inclusion into the medic's aid bag

Abstract: BACKGROUND:Many advancements in supraglottic airway technology have occurred since the start of the Global War on Terrorism. While the Tactical Combat Casualty Care guidelines previously recommend the i-gel device, this is based on little data and minimal enduser input. OBJECTIVE:We sought to use a mixed methods approach to investigate the properties of an ideal device for inclusion into the medic's aid bag. METHODS:We performed prospective, serial qualitative studies to uncover and articulate themes relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…With regards to the survey data, we found few significant differences across nearly all the survey questions, except for the comfort level in managing a potential transfusion reaction. This is not surprising as with previous studies, we have found little benefit with the quantitative survey data truly identifying key scientific findings 29 . However, the qualitative data indicated that most of the medics stated confidence in their skills regardless of how well they performed the procedure.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…With regards to the survey data, we found few significant differences across nearly all the survey questions, except for the comfort level in managing a potential transfusion reaction. This is not surprising as with previous studies, we have found little benefit with the quantitative survey data truly identifying key scientific findings 29 . However, the qualitative data indicated that most of the medics stated confidence in their skills regardless of how well they performed the procedure.…”
Section: Discussionsupporting
confidence: 75%
“…This is not surprising as with previous studies, we have found little benefit with the quantitative survey data truly identifying key scientific findings. 29 However, the qualitative data indicated that most of the medics stated confidence in their skills regardless of how well they performed the procedure. The use of a qualitative method design, while relatively novel for this population, is not a new area of science.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations